2017
DOI: 10.1021/acs.energyfuels.6b03059
|View full text |Cite
|
Sign up to set email alerts
|

Development of a High-Pressure Bubbling Sampler for Trace Element Quantification in Natural Gas

Abstract: A high-pressure bubbling sampler has been developed to trap and preconcentrate metals and metalloids from natural gas. This high-pressure sampler was designed to work at pressures up to 100 bar and be directly plugged into distribution and transportation networks. It consists of three vials in series, which contain 50 mL of metal trapping solution and the gas flows at the network pressure with a flow rate up to 40 L/min. The trapping solutions for mercury and other metals are permanganate/ sulfuric acid or nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…There are several approaches for separation, which often include use of solvents, hot water extractions (Jacobs and Filby, 1983) or acid digestions (Bicalho et al, 2017). Extracting volatile As species from natural gas is particularly challenging (Puri and Irgolic, 1989;Delgado-Morales et al, 1994b;Krupp et al, 2007;Xu et al, 2015;Cachia et al, 2017). Extraction methods include use of adsorption tubes or solutions (silver nitrate or nitric acid) to take up the volatile species such as trimethylarsine (TMA) from natural gas prior to analysis.…”
Section: Sampling and Analytical Methods For As In Hydrocarbonsmentioning
confidence: 99%
See 2 more Smart Citations
“…There are several approaches for separation, which often include use of solvents, hot water extractions (Jacobs and Filby, 1983) or acid digestions (Bicalho et al, 2017). Extracting volatile As species from natural gas is particularly challenging (Puri and Irgolic, 1989;Delgado-Morales et al, 1994b;Krupp et al, 2007;Xu et al, 2015;Cachia et al, 2017). Extraction methods include use of adsorption tubes or solutions (silver nitrate or nitric acid) to take up the volatile species such as trimethylarsine (TMA) from natural gas prior to analysis.…”
Section: Sampling and Analytical Methods For As In Hydrocarbonsmentioning
confidence: 99%
“…Most papers on methods focus on analyzing As in specific hydrocarbon sources, such as crude oil (Puri and Irgolic, 1989;Hardaway et al, 2004;Sánchez et al, 2013), oil sands (Bicalho et al, 2017), gasoline, diesel and naphtha (Brandão et al, 2006), and natural gas (Irgolic et al, 1991;Delgado-Morales et al, 1994b;Krupp et al, 2007;Xu et al, 2015;Cachia et al, 2017;Freije-Carrelo et al, 2017). As there are dozens of papers on analysis of As species in different hydrocarbon products, the reader is directed to these papers in addition to reviews (e. g., Nadkarni, 1991;Cassella et al, 2002;Sánchez et al, 2013) for more information.…”
Section: Sampling and Analytical Methods For As In Hydrocarbonsmentioning
confidence: 99%
See 1 more Smart Citation
“…To the authors' knowledge, biomethane has only been in situ sampled directly on the pipelines at the grid pressure (40 bar a ) by Cachia et al 22 using a high-pressure acid bubbling impinger for the direct preconcentration of metallic TC in gas samples. 31 So far, other reported determinations of TC in high-pressure gases (typically natural gas) have always been carried out by depressurization of the gas and preconcentration at atmospheric pressure: the gas is either depressurized in situ from the pipe aer what the sampling system is installed at atmospheric pressure, 32 or it is sampled at its grid pressure in surface-treated high-pressure stainless-steel cylinders subsequently transported to the lab for depressurization and preconcentration. 29,[33][34][35][36] Depressurization is detrimental to the preconcentration of TC since, assuming the ideal gas law PV ¼ nRT, a dilution factor equal to the ratio of the high pressure to the pressure aer depressurization leads to a concentration decrease of the TC, implying larger gas volumes have to sampled at atmospheric pressure than at high pressure to trap a given amount of TC.…”
Section: Introductionmentioning
confidence: 99%
“…These specifications ensure high quality gas for combustion but are also essential to prevent damage to facilities and protect consumer health. However, studies have revealed the presence of arsenic compounds, mercury and other metals/metalloids in natural gas from different origins at very low concentrations ranging from 10 −1 to 10 3 µg/m 3 [6][7][8][9][10][11]. These elements have well-known risks and potentially can cause industrial damage, such as through corrosion or catalytic poisoning.…”
Section: Introductionmentioning
confidence: 99%